Pozycja prawna ubezpieczającego w ubezpieczeniach na cudzy rachunek - Pawlak, Patryk (Wydawnictwo Naukowe UAM, 2020)
Celem niniejszego artykułu jest omówienie problematyki związanej z obowiązkami prawnymi wynikającymi z zawieranych umów ubezpieczenia na cudzy rachunek. Ostatnie zmiany prawne dotyczące branży ubezpieczeniowej skupiły się głównie na ubezpieczonym. Celem nowelizacji było wzmocnienie pozycji prawnej ubezpieczonego poprzez nadanie tymże podmiotom nowych praw podmiotowych. Cześć spośród nowelizowanych regulacji wywarła wskazany efekt, jednak praktyka rynku pokazała, iż ma to miejsce kosztem pozycji prawnej ubezpieczającego, co w istocie nadało poczynionym zmianom wiele kontrowersji. Artykuł przedstawia kilka problemów związanych z omawianymi nowelizacjami.

The aim of this paper is to highlight issues associated with legal obligations related to insurance agreements on someone else’s account. The recent legal changes regarding the issue of insurance are in most cases focused on the insured. The aim of the amendment was to provide the insured with more rights in order to strengthen its legal position. Many of those legislative changes are helpful and indeed required, but it often seems that the legal position of a policyholder is forgotten and, as a consequence, the amendments made are construed as controversial. The paper illustrates a few problems related with the discussed regulations.
Legal position of the policyholder in insurance contracts for someone else’s account
Keywords: prawo ubezpieczeniowe; insurance law; ubezpieczenia na cudzy rachunek; insurance contracts on someone else’s account; OWU; terms and conditions of insurance